Red Hat OpenShift container platform for IBM zCX - Parziale, Lydia; Armstrong, Andy; Cross, Vic; Havemann, Maike; Janssen, Redelf; Paniagua, Pablo; Kumar, Ravi (IBM Redbooks, 2022)
Application modernization is essential for continuous improvements to your business value. Modernizing your applications includes improvements to your software architecture, application infrastructure, development techniques, and business strategies. All of which allows you to gain increased business value from existing application code. IBM® z/OS® Container Extensions (IBM zCX) is a part of the IBM z/OS operating system. It makes it possible to run Linux on IBM Z® applications that are packaged as Docker container images on z/OS. Application developers can develop, and data centers can operate, popular open source packages, Linux applications, IBM software, and third-party software together with z/OS applications and data. This IBM Redbooks® publication presents the capabilities of IBM zCX along with several use cases that demonstrate Red Hat OpenShift Container Platform for IBM zCX and the application modernization benefits your business can realize.